2009
DOI: 10.1002/cbic.200800806
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Probes to Characterise FK506‐Binding Proteins

Abstract: Talented all-rounders: Fluorescence polarisation assays were developed for members of the FK506-binding protein family by using fluorescent rapamycin analogues (demonstrated in the figure). These tracers retain medium to high affinity to all tested proteins (FKBP12, -12.6, -13, -25, -51, -52). They can be used for active-site titrations, competition assays with unlabelled ligands and enable a robust, miniaturized assay adequate for high-throughput screening.FK506-binding proteins (FKBPs) convey the immunosuppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
125
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 81 publications
(133 citation statements)
references
References 73 publications
3
125
0
5
Order By: Relevance
“…These model organisms might therefore not suited to assess the contribution of the larger FKBPs. Intrigued by our initial finding that rapamycin can tightly bind to most members of the FKBP family, 14 we asked whether larger FKBP homologs contribute to the pharmacology of rapamycin in mammals. 15 We found that all tested human FKBPs (FKBP12, 12.6, 13, 25, 51, 52) could potently form rapamycin-induced ternary complexes with the FRB domain of mTOR and inhibit mTOR kinase activity.…”
Section: Fkbps the Enablers Of Rapamycinmentioning
confidence: 99%
“…These model organisms might therefore not suited to assess the contribution of the larger FKBPs. Intrigued by our initial finding that rapamycin can tightly bind to most members of the FKBP family, 14 we asked whether larger FKBP homologs contribute to the pharmacology of rapamycin in mammals. 15 We found that all tested human FKBPs (FKBP12, 12.6, 13, 25, 51, 52) could potently form rapamycin-induced ternary complexes with the FRB domain of mTOR and inhibit mTOR kinase activity.…”
Section: Fkbps the Enablers Of Rapamycinmentioning
confidence: 99%
“…An efficient fluorescence quenching of FKBP12 was observed upon addition of the ligands in solution. The dissociation constants, K d , for FK506 and Rfx were calculated according to literature and recent studies in our group [7,8] The ligands were embedded in a planar scaffold using a biomimetic approach: that is to say preparing Langmuir-Blodgett films of phospholipids. The optimal phospholipid composition for each ligand has been established from the analysis of previous literature [9] combined with our own experimental work.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids for the expression of His-tagged FKBPs in E. coli were prepared as described before (13). For expression in mammalian cell lines, cDNA of FKBPs was cloned into pcDNA3 (Invitrogen), and for expression in yeast cells, it was cloned into pYX223 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…5) (13). FK1706, a nonimmunosuppressive analog of FK506 (38) that tightly binds to FKBP12, as well as to FKBP51 (K i ϭ 50 nM) and to FKBP52 (K i ϭ 20 nM) (13,38), likewise blocked the effects of rapamycin. Biricodar (39) and compound 44 (40) are two structurally different substances that bind to FKBP12 almost as tightly as FK506 and FK1706 but more strongly discriminate against the larger FKBP51 and FKBP52 proteins (Ͼ500-fold selectivity for FKBP12).…”
Section: Numerous Fkbp-rapamycin Complexes Bind and Inhibit Mtormentioning
confidence: 99%
See 1 more Smart Citation